A comunidade imaginada do futebol. Estratégias midiáticas na enunciação esportiva - Oliveira, Maura de (2024)
In this article it is intended to approach the subject of the "Soccer game" and the strategies used by its presenters the sport narrators on constructing the sport announcement and, consequently, linking itself to the participants of the experiment of the mattered event, giving place in its reception to a feeling of "Imagined Community", concept developed by Benedict Anderson. Next to it, it is outlined considerations on the specificity of the sport announcement, exposing observed strategies as intrinsic in the process of production of this kind of speech.